SYLVATIC FOCUS OF TRICHINIASIS IN BANDAR ABBAS AREA SOUTH OF IRAN - A.N. Hamidi; I. Mobedi (Tehran University of Medical Sciences, 1977)
In 1969 and 1976, 237 rodents and carnivores collected from the Bandar abbas area South of Iran was examined fro Trichianella spiralis. 23% of foxes, 25% of stray dogs and all three captured golden jackals were found to be infected.